2024
DOI: 10.1146/annurev-earth-040722-104845
|View full text |Cite
|
Sign up to set email alerts
|

The Restructuring of Ecological Networks by the Pleistocene Extinction

Mathias Mistretta Pires

Abstract: Most terrestrial large mammals went extinct on different continents at the end of the Pleistocene, between 50,000 and 10,000 years ago. Besides the loss in species diversity and the truncation of body mass distributions, those extinctions were even more impactful to interaction diversity. Along with each extinction, dozens of ecological interactions were lost, reorganizing species interaction networks, which attained species-poor configurations with low functional redundancy. Extinctions of most large herbivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Taken together, these findings suggest that trophic structure, functional structure (as in Blanco et al, 2021) and species richness capture complementary aspects of the functional retailoring of communities over time. A simplification interaction networks has been described for abrupt biotic transition between terminal Pleistocene and early Holocene (Fricke et al, 2022;Pires, 2024;Pires et al, 2015), but in such cases, network restructuring was associated with human or climatedriven extinctions of the Pleistocene megafauna. Our results suggest that in the Iberian Peninsula, structural changes may have started far earlier and were not necessarily associated with overall reductions in species richness, but with a restructuring of the interactions due to changes in the faunal composition of the herbivore guild.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that trophic structure, functional structure (as in Blanco et al, 2021) and species richness capture complementary aspects of the functional retailoring of communities over time. A simplification interaction networks has been described for abrupt biotic transition between terminal Pleistocene and early Holocene (Fricke et al, 2022;Pires, 2024;Pires et al, 2015), but in such cases, network restructuring was associated with human or climatedriven extinctions of the Pleistocene megafauna. Our results suggest that in the Iberian Peninsula, structural changes may have started far earlier and were not necessarily associated with overall reductions in species richness, but with a restructuring of the interactions due to changes in the faunal composition of the herbivore guild.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few studies analysing a relatively long timeseries of reconstructed interaction networks spanning more than 800 thousand years, Nénzen et al (2014) showed that despite a high species turnover, the structure of interaction networks among terrestrial mammals in Europe changed little throughout the Pleistocene. Megafaunal extinctions at the terminal Pleistocene, however, resulted in secondary extinctions that simplified interaction networks, resulting in ecological systems that became progressively more vulnerable to species loss (Fricke et al, 2022;Nenzén et al, 2014;Pires, 2024;Pires et al, 2015). Other studies have used palaeoecological inferences to reconstruct interaction networks in Palaeozoic and Mesozoic communities showing, for instance, that food webs underwent marked structural changes during episodes of mass extinction (Angielczyk et al, 2005;Mitchell et al, 2012;Roopnarine et al, 2007Roopnarine et al, , 2019Roopnarine & Angielczyk, 2015).…”
Section: Introductionmentioning
confidence: 99%